2014
DOI: 10.1039/c3ra45013a
|View full text |Cite
|
Sign up to set email alerts
|

Role of graphene/metal oxide composites as photocatalysts, adsorbents and disinfectants in water treatment: a review

Abstract: With a rapidly growing population, development of new materials, techniques and devices which can provide safe potable water continues to be one of the major research emphases of the scientific community. While the development of new metal oxide catalysts is progressing, albeit at a slower pace, the concurrent and rapid development of high surface area catalyst supports such as graphene and its functionalised derivatives has provided unprecedented promise in the development of multifunctional catalysts. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
271
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(276 citation statements)
references
References 317 publications
(138 reference statements)
0
271
0
5
Order By: Relevance
“…The high specific surface areas, hydrophobic surface, and carbon defect active sites were found to be facilitative for the adsorption and activation of benzene, as well as the enhancement of catalytic activity of catalysts [27,31,35]. However, in spite of the fascinating two-dimensional structure of graphene with huge open π-electron systems, highly specific surface areas, and hydrophobic surface [27,36,37], to the best of our knowledge, few studies on the fabrication of uniform VO x nanoparticles (NPs) on graphene for the hydroxylation of benzene to phenol have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The high specific surface areas, hydrophobic surface, and carbon defect active sites were found to be facilitative for the adsorption and activation of benzene, as well as the enhancement of catalytic activity of catalysts [27,31,35]. However, in spite of the fascinating two-dimensional structure of graphene with huge open π-electron systems, highly specific surface areas, and hydrophobic surface [27,36,37], to the best of our knowledge, few studies on the fabrication of uniform VO x nanoparticles (NPs) on graphene for the hydroxylation of benzene to phenol have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The low adsorption capacity of Cr (VI) ions on the traditional adsorbents like activated carbon and high cost have restricted their wide applications (Dias et al 2007). On the other hand, graphene has been used as an efficient adsorbent to remove heavy metal ions from water or wastewater (Zhu et al 2011) because of its relatively low-cost, theoretically high surface area (*2,630 m 2 g -1 ), and high mesoporous volumes (Upadhyay et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Various active metal oxides nanoparticles, such as TiO2, ZnO, Cu2O and iron oxides, have been loaded on GO surface by in situ synthesis ( Figure 3) [13]. Bahnemann et aldegraded methylene blue by TiO2 loaded TiO2-GO, the photocatalytic degradation rates of MB by TiO2-GO were 3 times faster than that by P25 [18].…”
Section: Photocatalystsmentioning
confidence: 99%
“…Recent works have shown that GO can perform multiple roles in water and wastewater treatment including adsorbents, photocatalysts and membrane filtration [13]. …”
Section: Application Of Modified Graphene Oxide In Water Treatmentmentioning
confidence: 99%